PELATIHAN PENDAMPING OLIMPIADE MATEMATIKA SMP KABUPATEN TULUNGAGUNG - Budi P. Prawoto; Raden Sulaiman; Dian Savitri; Dini Kinati Fardah (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
This article discusses the activities of community service that raises the theme of mathematics olympiad training with the target is the teachers of math at junior level in Tulungagung regency. The reason for choosing this theme is to see competition in the increasingly rigorous world of education. School is aimed togive birth to outstanding students who can compete in the national, regional, and global arena. One of the problems faced in Tulungagung Regency related to junior high school mathematics is the lack of teachers or supervisors of the Olympics. Solutions offered to MGMP Matematika SMP Tulungagung is held training toteachers of mathematics junior high school for the future teachers can independently accompany students in the arena of mathematics olympiad. The response of the trainees' teachers showed a positive direction. The most important is the increasing insight or knowledge of the ins and outs of the mathematics olympiad.